The trouble with Jacob - McGraw, Eloise Jarvis (McElderry Books, 1988)
Twelve-year-old twins Andy and Kat think they are in for a dull summer at a remote resort in western Oregon, until the ghost of a nine-year-old boy appears demanding restitution for a crime committed over 100 years before.